2021
DOI: 10.3390/cells10071791
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of SUR2[A478V] Mutation in Skeletal Muscle of Murine Model of Cantu Syndrome

Abstract: (1) Background: Cantu syndrome (CS) arises from gain-of-function (GOF) mutations in the ABCC9 and KCNJ8 genes, which encode ATP-sensitive K+ (KATP) channel subunits SUR2 and Kir6.1, respectively. Most CS patients have mutations in SUR2, the major component of skeletal muscle KATP, but the consequences of SUR2 GOF in skeletal muscle are unknown. (2) Methods: We performed in vivo and ex vivo characterization of skeletal muscle in heterozygous SUR2[A478V] (SUR2wt/AV) and homozygous SUR2[A478V] (SUR2AV/AV) CS mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
(73 reference statements)
2
11
1
Order By: Relevance
“…Therefore, we propose that increased ZOL sensitivity in osteoblasts and soleus muscle likely reflects increased Kir6.1/SUR2B contributions to native KATP channels in these tissues relative to FBD and EDL muscle. Importantly, this is also consistent with our previous finding that the Kir6.1 V65M mutation, which reduces glibenclamide inhibition [ 11 ], has a greater effect on GLIB sensitivity of soleus KATP channels versus FDB KATP channels [ 9 ]. The high expression ratio of KCNJ8 -Kir6.1/ KCNJ11 -Kir6.2 relates to the potency of the zoledronic acid in the musculoskeletal tissues ( Table 2 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, we propose that increased ZOL sensitivity in osteoblasts and soleus muscle likely reflects increased Kir6.1/SUR2B contributions to native KATP channels in these tissues relative to FBD and EDL muscle. Importantly, this is also consistent with our previous finding that the Kir6.1 V65M mutation, which reduces glibenclamide inhibition [ 11 ], has a greater effect on GLIB sensitivity of soleus KATP channels versus FDB KATP channels [ 9 ]. The high expression ratio of KCNJ8 -Kir6.1/ KCNJ11 -Kir6.2 relates to the potency of the zoledronic acid in the musculoskeletal tissues ( Table 2 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, in Kir6.1 V65M mice, skeletal muscle was severely affected, muscles were atrophic and necrotic, and there was marked loss of muscle mass with fibrotic replacement, inflammatory cell infiltration, up-regulation of autophagy genes, and reduced muscle strength in slow twitch muscle, as well as severe impairment of glibenclamide response- [ 9 ]. These symptoms are very different from what previously observed in other neuromuscular disorders known as Hypokalemic Periodic Paralysis associated with the loss of function of the fast-twitch KATP channels in humans [ 11 , 13 ] and animals [ 14 , 15 ]. The human patients and the animals show muscle weakness with vacuolar features [ 16 ], but no necrosis or inflammation, and flaccid paralysis induced by insulin injection is associated with the lowering of extracellular K + ions concentration [ 17 , 18 ].…”
Section: Introductioncontrasting
confidence: 85%
See 1 more Smart Citation
“…The bone marrow cells from Kir6.1 (V65M) and the SUR2 (A478V) CS mice following differentiation failed to mineralize in our hands suggesting of abnormal mineralization process driven by the KATP channels. Histopathological analysis of femora bone sections from these mice, however, did not reveal severe abnormalities like those observed for instance in the skeletal muscles ( Scala et al, 2021 ; Scala et al, 2020a ) of the same animals, unless some osteoblasts aggregate were observed in some sections. We have demonstrated that CS mutation in the KCNJ8 genes encoding for the Kir6.1WT/VM is responsible for severe injuries in the skeletal muscle of a murine model of CS, reporting how GOF mutation caused atrophy, necrosis, and loss of muscle with fibrotic replacement, inflammatory cell infiltration, up-regulation of autophagy genes, and reduced muscle strength in the slow twitching muscle and impairment of glibenclamide response ( Scala et al, 2020b ).…”
Section: Introductionmentioning
confidence: 59%
“…We have demonstrated that CS mutation in the KCNJ8 genes encoding for the Kir6.1WT/VM is responsible for severe injuries in the skeletal muscle of a murine model of CS, reporting how GOF mutation caused atrophy, necrosis, and loss of muscle with fibrotic replacement, inflammatory cell infiltration, up-regulation of autophagy genes, and reduced muscle strength in the slow twitching muscle and impairment of glibenclamide response ( Scala et al, 2020b ). We also reported that in SUR2WT/AV and SUR2AV/AV mice, forelimb strength was reduced associated with loss of modulation of KATP channels by MgATP with metabolic decoupling and atrophy in different muscles ( Scala et al, 2021 ). A slight rightward shift of sensitivity to inhibition by glibenclamide was detected in SUR2AV/AV mice indicative however of a conserved response to this drug.…”
Section: Introductionmentioning
confidence: 93%